PENGARUH PENGGUNAAN MEDIA DIORAMA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP IPA MATERI EKOSISTEM PADA SISWA KELAS V SD NEGERI 13 SINGKAWANG - Sania Sania; Evinna Cinda Hendriana; Dewi Mariana (Journal of Educational Review and Research, 2024)
This study aims to (1) To determine the differences in the ability to understand science concepts of grade V students of SDN 13 Singkawang between the control and experimental classes, (2) To determine the effect of Diorama media on the Ability to Understand Science Concepts of students in grade V of SDN 13 Singkawang, (3) To determine students' responses to the use of diorama media in science learning for students in grade V of SDN 13 Singkawang. This type of research is quantitative with a quasi-experimental type with a non-equivalent pre-test and post-test control group design. The population in this study were all grade V students of SDN 13 Singkawang, totaling 47 people. Sampling in the study used a total sampling technique. Data collection techniques used test sheets and student response questionnaires. The data analysis technique used was a two-sample t-test and the results of the study showed that: (1). There is a difference in the Science Concept Understanding Ability of class V students of SDN 13 Singkawang between the control and experimental classes, this is shown by the results of t count 3.591 and t table 2.069. (2). The magnitude of the influence of Diorama Media on the Ability to Understand Science Concepts of students in class V of SD Negeri 13 Singkawang. This is proven by the results of the Effect Size test which shows that the value is 0,4, based on the criteria the value is 0,4 < 0,8, which means it is included in the medium criteria. (3) The student response questionnaire showed a very good response, as evidenced by the results of the percentage calculation getting a result of 82%.